Impact of Social and Economic Development on Mortality: Comparative Study of Kerala and West Bengal - Moni Nag (Economic and Political Weekly, Vol. 18, No. 19/21, Annual Number (May, 1983), 1983)
Kerala's mortality level has been lower than West Bengal's at least since the early 20th century. The difference became sharper in the 1970s. Environmental and hygienic conditions are more favourable in Kerala, but the difference does not seem to be great enough to explain a significant part of the mortality differential. The empirical evidence from various surveys shows that the differences between the states in nutritional standard, per capita income, distribution of income and assets, industrialisation and urban- isation, cannot explain the lower mortality level in Kerala. The wider distribution of health facilities in the rural areas of Kerala and their greater utilisation are found to be significant factors. Two important reasons why the health facilities are used more in Kerala have been identified. First, the proportion of literates, particularly among females, is much higher in Kerala. Historically there has always been greater emphasis in Kerala on education and public health. Secondly, the rural poor in Kerala are more aware of their rights to use health and other public facilities than those in West Bengal. The differential awareness can be traced to the historical difference in the social and political movements in the two states. In general, West Bengal has always been characterised by a higher level of economic development and Kerala by a higher level of social development. The lower mortality level in Kerala can be attributed mostly to its higher social development and partly to its favourable environmental and hygienic con- ditions